THE DAWKINS CHALLENGE: with Bethany Sollereder, "Introduction to Essays in Honor of Alister McGrath"; Peter Harrison, "What is Natural Theology? (And Should We Dispense with It?)"; John Hedley Brooke, "Revisiting William Paley"; Helen De Cruz, "A Taste for the Infinite: What Philosophy of Biology Can Tell Us about Religious Belief"; Michael Ruse, "The Dawkins Challenge"; Donovan O. Schaefer, "The Territories of Thinking and Feeling: Rethinking Religion, Science, and Reason with Alister McGrath"; Andrew Pinsent, "Alister McGrath and Education in Science and Religion"; Andrew Davison, "Science and Specifity: Interdisciplinary Teaching between Theology, Religion, and the Natural Sciences"; Victoria Lorrimar, "Does an Inkling Belong in Science and Religion? Human Consciousness, Epistemology, and the Imagination"; and Alister E. McGrath, "Response: Science and Religion—The State of the Art.". Issue 1 (29th December 2021) - Ruse, Michael
Abstract: Richard Dawkins, in his The God Delusion, argued strongly for atheism. Alister McGrath picked up the challenge and argued that Dawkins is wrong and that his arguments are very weak. This article, part of a symposium honoring McGrath looks in detail at the God Delusion, and at two books by McGrath, Dawkins' God, written before T he God Delusion appeared but addressing the arguments of that book, and The Dawkins' Delusion, co‐authored with his wife Joanna Collicutt McGrath that appeared after T he God Delusion . It is argued that the debate is still timely and that sociological factors are extremely important.